Pengaruh Pembiayaan Murabahah Terhadap Profitabilitas Pada PT Bank BSI KCP Binjai - Dinda Rudang Sari Sembiring; Ahmad Fuadi; Khairani Sakdiah (Al-Sharf: Jurnal Ekonomi Islam, 2022)
This research aims to analyze how murabahah financing affects profitability at PT Bank BSI KCP Binjai. This type of research is field research conducted at PT Bank BSI Binjai using quantitative descriptive methods. The data collection technique that the author uses is documentation in the form of financial statements of PT bank BSI Binjai in 2015-2019. Data analysis using SPSS 22. The results showed that murabahah financing to ROA profitability at PT Bank BSI Binjai did not have a significant effect on the correlation coefficient between murabahah financing and profitability of 0.705 which means a positive and strong correlation to profit, while the simple linear regression coefficient of murabahah financing to profit is 0.369 and the standard regression coefficient is 0.214. Based on both numbers obtained thitung = 1.723. While the critical value according to the table uses the formula t α df n-2 which is 0.05 df 5-2 = 3. Because thitung is smaller than ttabel (1,723 <3,182) at a significant level of 0.05, Ho is accepted, meaning that there is no significant influence between murabahah financing and profitability (ROA) on PT Bank BSI Binjai.